2020
DOI: 10.1007/s00167-020-05866-0
|View full text |Cite
|
Sign up to set email alerts
|

Difficult primary total knee arthroplasty requiring a varus–valgus constrained implant is at higher risk of periprosthetic infection

Abstract: Purpose The goal of this study was to compare the risk of periprosthetic infection of a consecutive cohort of primary varusvalgus constrained (VVC) total knee arthroplasties (TKAs), with a matched 1:1 cohort of primary posterior-stabilized (PS) TKAs. Methods 74 primary VVC TKAs performed in 66 patients were identiied and matched 1:1 with a cohort of 74 primary PS TKAs performed in 73 patients. At last follow up, patients were clinically evaluated using the Knee Society Score (KSS). Kaplan-Meier survival curves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Therefore, this demonstrated that CCK without stem extension did not have a markedly negative effect on implant survivorship among patients with adequate bone quality. Furthermore, Costa et al 28 reported that stemmed CCK implants were at a higher revision rate due to periprosthetic infection, which was further confirmed by the present study.…”
Section: Implant Survivorshipsupporting
confidence: 89%
“…Therefore, this demonstrated that CCK without stem extension did not have a markedly negative effect on implant survivorship among patients with adequate bone quality. Furthermore, Costa et al 28 reported that stemmed CCK implants were at a higher revision rate due to periprosthetic infection, which was further confirmed by the present study.…”
Section: Implant Survivorshipsupporting
confidence: 89%
“…The VVC prosthesis system was designed to have more constraints than the PS but fewer constraints than the hinge implant. Compared with the number of studies on the outcomes and survival of VVC prostheses in complex primary TKA and aseptic revision, 20,21 there is a paucity of studies reporting the survival of VVC implants following revision for infection. To our knowledge, only one study reported the outcomes of two-stage revision, 22 and no studies reported the outcomes of one-stage revision.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rates of the prostheses in this study were better than those in earlier reports and were comparable to those in recent reports. The failure rate for the VVC prosthesis used in the primary TKAs ranged from 0 to 22%, 20,26,27 and the rate ranged from 0 to 35.7% for revisions. 22,27,28 In the only study that has reported the outcomes of two-stage revision using the VVC implant, Wilke et al 22 reported a case with 71% overall 5-year survival and an estimated 64% 10-year survival when repeat revision surgery was used as the end point.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although surgical treatment, such as arthroplasty, is an effective method for the treatment of osteoarthritis, the risks of surgery and the acceptance of patients need to be considered by clinical staff. 3,4 The management of osteoarthritis should be based on individualized approaches. 5 Clinicians should identify and manage the risk factors that lead to patients' conditions, which can effectively improve their joint metabolism and biomechanical state to relieve joint pain and delay surgical interventions.…”
Section: Introductionmentioning
confidence: 99%